Saber sobre promoción de la salud en familias y personal de salud - Reátegui Del Castillo, Elva Lorena (2008)
The present doctor thesis in Public health, whose main purpose was to analyze the knowledge about promotion of the health in families and personnel from San Juan in Loreto and its objectives are to analyze these knowledge and discuss if is possible to articulate them or not. The theoretical frame is based in knowing conception of JAPIASSU (1991), the dialogical, education of FREIRE (2000), the praxis’ philosophy of GRAMSCI (1981), promotion the health´s of FRANCO (1995), AROUCA (2003) and GARCIA (2005). The qualitative investigation was developed according to creative and sensitive method of CABRAL (1998) which creative and sensitive dynamic (calendar) was developed in four meetings: Two whit the families and two with the families and two with the personnel, doing a whole of 29 participants. The analysis of the information, have being realized with the analysis of speech principles according to ORLANDI (1997). The result of the thesis shawed that the dialog between families and the personnel developed the knowledge about healt`s promotion which is a structure by two dimensions: social and technical. The knowledge of the families is inherent to its sociocultural formation and to its integral philosophy, which result have being the first category of analysis: social dimension where the speeches shawed us that the health is a basic necessity and the promotion of the health it is to cowe the enviroment, prevent ilnesses and paternalism The Knowledge of the personnel is inherent to its academic formation and to its lineal philosophy, which result have being the second category: Thecnical dimension and the first topic: the conception about health. The mayority of speeches identify the conception about health with the conception of the World Health Organization that consider “that the health is a complete physical, mental and social well-being and it`s not only the absence of illness”. Also, the conception about the promotion of health, that is related with orientation, education, awareness and to expand the service, increase service, control and prevent illness. The training of the personnel about the promotion of health shows the work with the population, authorities as soon as the educational work about expansion, orientation, fumigation and vaccination.